2013
DOI: 10.1080/00032719.2013.805415
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Sample Preservation Methods for the Determination of Stable Carbon and Nitrogen Isotope Ratios in Mollusks

Abstract: The aim of this study was to quantify the effects of preservation methods and preservation times on the stable carbon and nitrogen isotope values in the tissues of six mollusk species (Mytilus edulis, Crassostrea gigas, Ruditapes philippinarum, Acanthochiton seulschnochilon, Littorina brevicula, and Rapana venosa). To identify potential preservation effects on d 13 C and d 15 N values and to examine temporal changes in the effects of preservation, repeated analyses were carried out after 1 day, 5 days, 15 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…Such δ 15 N enrichment by ethanol was previously reported in several studies of fish (Sweeting et al 2004, Kelly et al 2006) and molluscs (e.g. Syväranta et al 2011, Liu et al 2013. Because ethanol could cause tissue hydrolysis and leaching (Sarakinos et al 2002), we infer that 70% ethanol effectively extracted certain constituents containing nitrogen from the muscle tissue in addition to lipids.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Such δ 15 N enrichment by ethanol was previously reported in several studies of fish (Sweeting et al 2004, Kelly et al 2006) and molluscs (e.g. Syväranta et al 2011, Liu et al 2013. Because ethanol could cause tissue hydrolysis and leaching (Sarakinos et al 2002), we infer that 70% ethanol effectively extracted certain constituents containing nitrogen from the muscle tissue in addition to lipids.…”
Section: Discussionmentioning
confidence: 48%
“…Sweeting et al 2004. Kelly et al 2006, Syväranta et al 2011, Liu et al 2013. We attribute this effect to the substance extraction process, since subsequent lipid extraction treatment (ET-LE) substantially reduced this variation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gathering samples from food‐web members presents some practical problems that complicate the interpretation of food‐web structure from isotopes. Drying samples immediately from a fresh state is the preferred method of sample preparation for isotopic analysis because it is free from preservative effects and specimens can be stored for extended periods of time in a dried state . However, conditions in the field often make immediate processing impossible, so sample preservation is usually required to prevent decomposition and associated isotopic fractionation of samples before they can be processed in the laboratory …”
mentioning
confidence: 99%
“…Drying samples immediately from a fresh state is the preferred method of sample preparation for isotopic analysis because it is free from preservative effects and specimens can be stored for extended periods of time in a dried state. [2,9] However, conditions in the field often make immediate processing impossible, so sample preservation is usually required to prevent decomposition and associated isotopic fractionation of samples before they can be processed in the laboratory. [10,11] Considerable research has demonstrated that chemical preservatives (e.g., alcohol) and fixatives (e.g., formalin) can shift the isotope ratios of aquatic organisms but not in a systematic way.…”
mentioning
confidence: 99%